The adjunctive effect of probiotics to nonsurgical treatment of chronic periodontitis: A randomized controlled clinical trial - Ghadeer Khalil Mohamed El-bagoory; Hoda Mohamed El-guindy; Malak Yousef Mohamed Shoukheba; Enas Arafa El-zamarany (Wolters Kluwer Medknow Publications, 2021)
Background: Probiotics catch more attention as adjunctive periodontal therapy. This study was conducted to assess the benefit of locally delivered Lactobacillus reuteri (L. reuteri) probiotic as an adjunctive to scaling and root planing (SRP) in the treatment of chronic periodontitis clinically and microbiologically. Materials and Methods: Bacterial cultures and clinical evaluation were recorded in 20 sites of chronic periodontitis in 12 patients and followed up at 3 and 6 months from the start of intervention using clinical attachment level, probing pocket depth, plaque index (PI), bleeding on probing, and microbiologically for Porphyromonas gingivalis (P. gingivalis) load. Patients meeting the inclusion criteria were scheduled within 1 week for two sessions of SRP. After SRP, oral hygiene measures were reassured, and sites were divided randomly into two groups 10 sites each. Group I received SRP only, while Group II received SRP and subgingival delivery of 1 ml of probiotic L. reuteri suspension at baseline and 1, 2, and 4 weeks using a blunt syringe. A periodontal pack was applied after the placement of the drug. Results: We found noticeable variation between the two groups in all evaluation aspects at 3 and 6-month follow-up periods except PI at 6 months in which there was no significant difference between both groups. Conclusions: The results proved the antimicrobial benefit of L. reuteri probiotic as a promising adjunctive therapy in improving periodontal parameters. However, further long-term studies with large sample size are needed to evaluate the extent of the added value of L. reuteri suspension.